Fluorinated Nucleotide Modifications Modulate Allele Selectivity of SNP-Targeting Antisense Oligonucleotides - Michael E. Østergaard; Josh Nichols; Timothy A. Dwight; Walt Lima; Michael E. Jung; Eric E. Swayze; Punit P. Seth (Elsevier, 2017)
Antisense oligonucleotides (ASOs) have the potential to discriminate between subtle RNA mismatches such as SNPs. Certain mismatches, however, allow ASOs to bind at physiological conditions and result in RNA cleavage mediated by RNase H. We showed that replacing DNA nucleotides in the gap region of an ASO with other chemical modification can improve allele selectivity. Herein, we systematically substitute every position in the gap region of an ASO targeting huntingtin gene (HTT) with fluorinated nucleotides. Potency is determined in cell culture against mutant HTT (mtHTT) and wild-type HTT (wtHTT) mRNA and RNase H cleavage intensities, and patterns are investigated. This study profiled five different fluorinated nucleotides and showed them to have predictable, site-specific effects on RNase H cleavage, and the cleavage patterns were rationalized from a published X-ray structure of human RNase H1. The results herein can be used as a guide for future projects where ASO discrimination of SNPs is important.